Vengeance in Venice - Neubauer, Erica Ruth, 1979- (Neubauer, Erica Ruth, 1979- Jane Wunderly mysteries, 2026)
"At long last, Jane and Redvers have arrived in Venice, the famed city of love, for their honeymoon. But behind a mask at a costume ball on the Grand Canal hides the gaze of a heartless killer... Venice, 1927: As romantic as it is myserious, the Floating City is a dream destination for the newlyweds, but they'll soon discover the twisting canals hide more mystery than expected. It begins when they are invited to an elaborate party at Clara Morton's stunning palazzo on Grand Canal. The affair is as eccentric as the hostess, who is dressed as Medusa, and features everything from snakes to her pet cheetah to tarot card readings. The fête also features a fresh corpse--Clara's ex-husband, found dead in the garden with marks around his neck. The hostess accuses the tarot card reader, who happens to be an acquaintance of Jane, claiming the woman foretld the death of someone close to her. Jane and Redvers come to the young woman's aid as they learn she was far from the only partygoer with a motive. As the couple follows a labyrinthine trail of scandalous affairs, brazen blackmail, and people who are not who they say they are, they hope that Venice will disclose her secrets before they both end up over their heads." -- page 2 of cover